A STUDY OF CADMIUM INCORPORATION INTO PYRRHOTITES OF DIFFERENT STOICHIOMETRY - Tauson V.L.; Akimov V.V.; Parkhomenko I.Yu.; Nepomnyashchikh K.V.; Men'shikov V.I. (My University, 2004)
The results of experimental and theoretical study of one of the main principle of recent endocrypty concept [1] is reported here. The principle says that the incorporation limit for an element depends on the type and concentration of structural defects. Cadmium was used as a model element, for which a specially designed scheme of thermal atomic absorption analysis is applied for separation of the modes of its occurrence. Pyrrhotite simulates a phase with high concentration of structural vacancies. It was determined that Cd solubility in the nonstoichiometric pyrrhotite at 600 and 700°C is two orders of magnitude higher than that in the stoichiometric one. Using the model of concentrational expansion of elastic medium with incorporation of such dilatation centers as vacancies, isomorphous substitution impurities, and elastic dipoles (vacancy + impurity), we obtained an expression for the calculation of the concentration of Cd atoms interacting with vacancies. The models of Fe substitution for Cd in octahedral sites and Cd incorporation in tetrahedral interstitial sites yield nearly identical results. The theory correctly describes the qualitative dependence of the Cd incorporation limit in pyrrhotites on the concentration of Fe vacancies and temperature, but shows inconsistency with the real solubility values. This can be related to the specific features of troilite structure and the assumptions accepted in calculations.